Genetic Diversity Analysis in Rapeseed-Mustard using Quality Characters - Chauhan, J S; Bhadauria, V PS; Singh, K H; Singh, Maharaj; Singh, Arvind (Annals of Arid Zone, 2016)
A two-year study was carried out during 2003-04 and 2004-05 using 40 varieties of rapeseed-mustard to assess genetic divergence by Mahalanobis statistic, on the basis of oil and seed meal quality characters. Highly significant differences among the genotypes for the total 9 characters (X2 = 752.2 at 351 degree of freedom) were revealed by the analysis using V statistics of dispersion for the test of significance of differences in the mean values based on Wilke’s criterion. Based on the relative magnitude of D2 values, 40 rapeseed-mustard varieties were grouped into 8 clusters, I being the largest having 29 varieties. The cluster I accommodated 23 mustard, 4 toria and 1 karan rai and 1 yellow sarson varieties. Cluster VI contained 4 gobhi sarson varieties. Clusters II, IV, V, VII and VIII were mono-genotypic. Except cluster I, the rest of the clusters were crop-specific. The intra-cluster distance ranged from 0.0-4.6 and the inter cluster distance varied between 4.3-8.9. The contribution of different quality characters towards divergence indicated that eicosenoic acid contributed the least (2.8%) and the protein content contributed maximum (26.5%) to the total divergence among the varieties investigated. The implications of these results in quality improvement program are discussed in this paper. Key words: Rapeseed-mustard, Brassica species, quality characters, 02 statistic, genetic divergence.